2014
DOI: 10.3389/fnsys.2014.00010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mild-to-moderate hearing loss on auditory and emotion processing networks

Abstract: We investigated the impact of hearing loss (HL) on emotional processing using task- and rest-based functional magnetic resonance imaging. Two age-matched groups of middle-aged participants were recruited: one with bilateral high-frequency HL and a control group with normal hearing (NH). During the task-based portion of the experiment, participants were instructed to rate affective stimuli from the International Affective Digital Sounds (IADS) database as pleasant, unpleasant, or neutral. In the resting state e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
117
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(131 citation statements)
references
References 58 publications
9
117
2
3
Order By: Relevance
“…There is a growing body of evidence that the STG is also involved in perception of emotions (de Greck et al, 2012;Husain et al, 2014;Pehrs et al, 2013;Robins et al, 2009). In one fMRI study increased activation in the bilateral STG was observed in response to pleasant or unpleasant sounds when compared to neutral sounds (Husain et al, 2014); HCs showed increased activation in the left STG specifically while listening to pleasant or unpleasant sounds, compared to neutral sounds.…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)mentioning
confidence: 97%
“…There is a growing body of evidence that the STG is also involved in perception of emotions (de Greck et al, 2012;Husain et al, 2014;Pehrs et al, 2013;Robins et al, 2009). In one fMRI study increased activation in the bilateral STG was observed in response to pleasant or unpleasant sounds when compared to neutral sounds (Husain et al, 2014); HCs showed increased activation in the left STG specifically while listening to pleasant or unpleasant sounds, compared to neutral sounds.…”
Section: Increased Fa In Superior Temporal Gyrus (Stg)mentioning
confidence: 97%
“…This strongly suggests that tinnitus patients process acoustic signals on an emotional level, which is different from the processing by control subjects and independent from the genuine emotional value of the stimuli, suggesting stronger involvement of the limbic (resting state) network. Further evidence supporting such a processing system includes more pronounced involvement of the emotional and auditory network seen in tinnitus patients and advanced involvement of several attention networks (specifically the executive control of attention) in the control subjects [Husain et al, 2014]. These networks possibly contribute to the tinnitus-related stress, insomnia, anxiety, tension and depression, and may have a reinforcing effect on tinnitus or induce formation of negative connections that drive supporting feedback circles.…”
mentioning
confidence: 99%
“…In the control subjects, these regions are active only during processing of the affective stimuli (beeps and words) and here show a greater connectivity between limbic areas and other cortical networks. In several studies, tinnitus patients show in resting state networks modifications and increased connectivity between attention and auditory processing in the brain [Husain et al, 2014]. Activation of the frontal regions reflects executive functions together with emotional processing and attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Presbycusis is the third most prevalent pathology in this age group, behind only arthritis and arterial hypertension 7 . The high prevalence of hearing loss among the elderly may be explained by numerous factors such as mutations of mitochondrial DNA, genetic disorders, hypertension, diabetes, metabolic and other systemic diseases.…”
Section: Introductionmentioning
confidence: 99%